2009
DOI: 10.1021/jp901142q
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectrum and Electronic Properties of a Noncentrosymmetric Chalcopyrite Compound HgGa2S4: LDA, GGA, and EV-GGA

Abstract: An all electron full potential linearized augmented plane wave method has been applied for a theoretical study of the band structure, density of states, and electron charge density of a noncentrosymmetric chalcopyrite compound HgGa(2)S(4) using three different approximations for the exchange correlation potential. Our calculations show that the valence band maximum (VBM) and conduction band minimum (CBM) are located at Gamma resulting in a direct energy gap of about 2.0, 2.2, and 2.8 eV for local density appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…2 shows the band structure of the alloys for various Te content. For the cubic structure with the increasing Te content the band gap is decreased in agreement with the previous calculations using the same approach [7] Previous studies [27,28] have shown that the use of the LDA and GGA usually leads to underestimate the energy band gaps in semiconductors. Moreover, both of LDA and GGA functional are based on simple model assumptions which are not sufficiently flexible for accurate reproduction of the exchange correlation energy and its charge space derivative.…”
Section: Band Structure and Density Of Statessupporting
confidence: 84%
“…2 shows the band structure of the alloys for various Te content. For the cubic structure with the increasing Te content the band gap is decreased in agreement with the previous calculations using the same approach [7] Previous studies [27,28] have shown that the use of the LDA and GGA usually leads to underestimate the energy band gaps in semiconductors. Moreover, both of LDA and GGA functional are based on simple model assumptions which are not sufficiently flexible for accurate reproduction of the exchange correlation energy and its charge space derivative.…”
Section: Band Structure and Density Of Statessupporting
confidence: 84%
“…Borate materials, which are crystallographic noncentrosymmetric (NCS), have attracted considerable interest for their potential characteristics, especially in the second-order nonlinear optical (NLO) activity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Introducing NCS building units has become an extremely important way of obtaining NCS structures, 18,[19][20][21][22][23][24] such as acentrically distorted units with octahedral coordinated d 0 transition metals (Nb 5+ , V 5+ , etc.) or lone-pair active cations (Pb 2+ , Bi 3+ ) due to the second-order Jahn-Teller (SOJT) effect.…”
Section: Introductionmentioning
confidence: 99%
“…At a pressure of about 13 GPa the BCT phase has also been reported to undergo a rocksalt‐type phase transition 4. Recently, a growing interest has been shown in the study of these tetrahedrally bonded materials because of their wide optoelectronic, electro‐optic, and nonlinear device applications 5–7. The Hg‐related defect chalcopyrite compounds such as HgGa 2 S 4 and HgAl 2 Se 4 are getting more attention because of high nonlinear susceptibility, low absorption coefficient, and considerable birefringence 7.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing interest has been shown in the study of these tetrahedrally bonded materials because of their wide optoelectronic, electro‐optic, and nonlinear device applications 5–7. The Hg‐related defect chalcopyrite compounds such as HgGa 2 S 4 and HgAl 2 Se 4 are getting more attention because of high nonlinear susceptibility, low absorption coefficient, and considerable birefringence 7. Systematic studies on the variation of different thermophysical properties of defect chalcopyrite have gained considerable interest among solid‐state physicists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation